2017
DOI: 10.1038/srep46560
|View full text |Cite|
|
Sign up to set email alerts
|

The peripheral blood proteome signature of idiopathic pulmonary fibrosis is distinct from normal and is associated with novel immunological processes

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal interstitial pneumonia. The disease pathophysiology is poorly understood and the etiology remains unclear. Recent advances have generated new therapies and improved knowledge of the natural history of IPF. These gains have been brokered by advances in technology and improved insight into the role of various genes in mediating disease, but gene expression and protein levels do not always correlate. Thus, in this paper we apply a novel large scale hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 61 publications
5
53
0
Order By: Relevance
“…IPF aetiology and pathogenesis are poorly understood . The disease results in aberrant accumulation of extracellular matrix within the interstitium of the lung, promoting impaired gas exchange and respiratory failure …”
Section: Proteomic Applications In Respiratory Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…IPF aetiology and pathogenesis are poorly understood . The disease results in aberrant accumulation of extracellular matrix within the interstitium of the lung, promoting impaired gas exchange and respiratory failure …”
Section: Proteomic Applications In Respiratory Diseasementioning
confidence: 99%
“…31 SOMAmers have been used to develop biomarker tools in several forms of respiratory disease including lung cancer, [32][33][34] pulmonary tuberculosis 35,36 and idiopathic pulmonary fibrosis (IPF). 37,38…”
Section: Aptamer-based Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The speculation in the case of these mutations is that impaired or altered host defense may impair pathogen clearance and allow damage to the lung epithelium. Our recent work has also demonstrated that levels of circulating proteins associated with host defense response are downregulated in IPF patients further supporting impaired immunity as a key feature of disease pathology [57]. Given this supposition, it is especially interesting that recent studies have suggested that the lung microbiome is altered in patients with IPF.…”
Section: Introductionmentioning
confidence: 96%